2022
DOI: 10.1007/s11060-021-03893-6
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Laser Ablation (SLA) followed by consolidation stereotactic radiosurgery (cSRS) as treatment for brain metastasis that recurred locally after initial radiosurgery (BMRS): a multi-institutional experience

Abstract: Introduction: The optimal treatment paradigm for brain metastasis that recurs locally after initial radiosurgery (BMRS) remains an area of active investigation. Here, we report outcomes for patients with BMRS treated with stereotactic laser ablation (SLA, also known as laser interstitial thermal therapy, LITT)followed by consolidation radiosurgery (cSRS).Methods: Clinical outcome of 20 patients with 21histologically con rmed BMRS treated with SLA followed by consolidation SRS and >6 months follow-up were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
(51 reference statements)
0
3
0
Order By: Relevance
“… 12–14 There is increasingly compelling evidence supporting the efficacy of SLA as a treatment for primary brain cancer 2 , 14–16 and metastatic brain cancers. 5 , 17 , 18 An emerging theme in this literature is that the extent of ablation constitutes a major determinant of efficacy. In this context, the treatment of multifocal neoplastic diseases, exemplified by the case presented here, presents a technical challenge.…”
Section: Discussionmentioning
confidence: 99%
“… 12–14 There is increasingly compelling evidence supporting the efficacy of SLA as a treatment for primary brain cancer 2 , 14–16 and metastatic brain cancers. 5 , 17 , 18 An emerging theme in this literature is that the extent of ablation constitutes a major determinant of efficacy. In this context, the treatment of multifocal neoplastic diseases, exemplified by the case presented here, presents a technical challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The case series of 20 patients treated with LITT and SRT reported by Peña Pino et al demonstrated 100% local control rates at 6 and 12 months. 41 While SRT is a widespread first-line treatment for the management of single and multiple brain metastases, recurrent tumor and RN occur in 5%–15% of SRT-treated brain lesions. 42 , 43 As OS continues to improve with the advent of more effective systemic therapies, the management of recurrent disease presents a growing neuro-oncologic challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the overall survival was prolonged to 23.2 months after receiving the therapy 189 ( Figure 4A–G ). In 2022, Chen et al combined stereotactic laser ablation (SLA) and consolidation stereotactic radiosurgery (cSRS) to treat brain tumors metastasized from lung cancer, breast cancer, gastrointestinal cancer, melanoma cancer, ovarian cancer, urothelial cancer, and laryngeal cancer 190 in a study involving 20 patients. They injected 5–6 Gy MNPs and heated them to 43–60°C.…”
Section: Magnetothermal Therapy Using Mnpsmentioning
confidence: 99%